Extracting parameters from current-voltage characteristics of pentacene field-effect transistor in saturation region - Yakuphanoğlu, Fahrettin; Mansouri, S.; Bourguiga, R. (Elsevier Science Sa, 2012)
The pentacene thin film transistor was fabricated on a SiO2 layer by thermal evaporation method. Using the variable range hopping model (VRH), we have calculated the mobility of carrier charges in saturation region. The electrical parameters, conductance g(ch) and the total resistance R-T, of the pentacene transistor were extracted using a differential method based on first and second numerical derivatives of electrical measurement. The obtained results are in good agreement with the experimental results. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Organics TFTs; Mobility; Modeling